Comparative Effectiveness of Risk-Stratified Care Management in Reducing Readmissions in Medicaid Adults With Chronic Disease. Issue 1 (January 2016) - Hewner, Sharon; Wu, Yow-Wu Bill; Castner, Jessica
Abstract : Abstract: Hospitalized adult Medicaid recipients with chronic disease are at risk for rehospitalization within 90 days of discharge, but most research has focused on the Medicare population. The purpose of this study is to examine the impact of population-based care management intensity on inpatient readmissions in Medicaid adults with pre-existing chronic disease. Retrospective analyses of 2, 868 index hospital admissions from 2012 New York State Medicaid Data Warehouse claims compared 90-day post-discharge utilization in populations with and without transitional care management interventions. High intensity managed care organization interventions were associated with higher outpatient and lower emergency department post-discharge utilization than low intensity fee-for-service management. However, readmission rates were higher for the managed care cases. Shorter time to readmission was associated with managed care, diagnoses that include heart and kidney failure, shorter length of stay for index hospitalization, and male sex; with no relationship to age. This unexpected result flags the need to re-evaluate readmission as a quality indicator in the complex Medicaid population. Quality improvement efforts should focus on care continuity during transitions and consider population-specific factors that influence readmission. Optimum post-discharge utilization in the Medicaid population requires a balance between outpatient, emergency and inpatient services to improve access and continuity.